2008
DOI: 10.1093/intimm/dxn058
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant surfactant protein-D selectively increases apoptosis in eosinophils of allergic asthmatics and enhances uptake of apoptotic eosinophils by macrophages

Abstract: Pulmonary surfactant protein-D (SP-D) is a multifunctional, pattern recognition molecule involved in resistance to allergen challenge and pulmonary inflammation. In view of therapeutic effects of exogenous SP-D or recombinant fragment of human surfactant protein-D (rhSP-D) (composed of eight Gly-X-Y collagen repeat sequences, homotrimeric neck and lectin domains) in murine models of lung allergy and hypereosinophilic SP-D gene-deficient mice, we investigated the possibility of a direct interaction of purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 55 publications
3
43
0
1
Order By: Relevance
“…The multimeric form of SP-D binds to eosinophils in a saturable, calcium-and carbohydrate-dependent manner and increases apoptosis (32,36). However, there is an association between SP-D expression and eosinophilia (37) and SP-D-deficient mice display reduced symptoms in an Aspergillus-mediated model of asthma (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multimeric form of SP-D binds to eosinophils in a saturable, calcium-and carbohydrate-dependent manner and increases apoptosis (32,36). However, there is an association between SP-D expression and eosinophilia (37) and SP-D-deficient mice display reduced symptoms in an Aspergillus-mediated model of asthma (38).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we also found that increased BAL eosinophilia was positively correlated with BAL SP-D level within challenged patients with asthma. Mechanistically, this may result from a loss of the ability of SP-D to bind to and promote apoptosis of eosinophils (36), because both the increase in eosinophil number and SP-D level was greatest in those patients whose SP-D had become oxidatively cross-linked. In this regard it is interesting to note that SNO-SP-D has a reduced ability to inhibit eotaxin-mediated eosinophil chemotaxis ( Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic potential of recombinant human surfactant protein D (rhSP-D) has been established by studies in murine models of lung allergy, hypereosinophilic SP-D gene-deficient mice and also with eosinophils from allergic patients. These studies clearly suggest therapeutic application of rhSP-D for allergic and invasive diseases [32][33][34][35][36][37]. Single nucleotide polymorphisms (SNPs); have been observed in these genes (SP-A, SP-D and MBL).…”
Section: Interesting Biomolecules Of Aspergillimentioning
confidence: 86%
“…Cependant, l'action de SP-D sur les éosinophiles est dépendante de leur activation : il y a une sélectivité de SP-D pour les éosinophiles activés car ils ont moins de récepteurs inhibiteurs à leur surface, ce qui permet l'action de la protéine [32]. La sélectivité de SP-D vis-à-vis des éosinophiles activés a ainsi été démontrée chez l'homme, avec une corrélation entre l'augmentation du taux de protéine cationique des éosinophiles (ECP) dans le sputum et l'augmentation du taux de SP-D sérique après challenge allergénique dans une petite cohorte de patients adultes asthmatiques.…”
Section: Les Protéines a Et D Du Surfactant (Sp-a Et Sp-d) Sont Des Punclassified